Antimicrobial use regulations are associated with increased susceptibility among bovine Salmonella isolates from a U.S. surveillance system - Claudia Cobo-Angel; Maya Craig; Marwan Osman; Kevin J. Cummings; Casey L. Cazer (One Health)
Health authorities around the world have called to limit antimicrobial use in food-producing animals. In the United States, two recent regulatory actions have changed the use of antimicrobials in livestock, banning production uses in 2017 and restricting extra-label use of cephalosporins in 2012. This study aimed to assess the impact of the 2012 and 2017 regulations on antimicrobial use in cattle in the United States by analyzing 18,627 bovine Salmonella AMR susceptibility patterns using data from the National Antimicrobial Resistance Monitoring System (NARMS). Logistic regression was used to model the odds of being a susceptible isolate. Additionally, interval-censored accelerated failure time (AFT) models were used to analyze changes in minimum inhibitory concentrations (MICs) over time and by serotype. The most common serotypes were Montevideo (n = 3003), Anatum (n = 1394), Cerro (n = 1373), and Typhimurium (n = 1213). Susceptibility was highest for azithromycin (99 %), ciprofloxacin, gentamicin, and trimethoprim-sulfamethoxazole (all 98 %), and lowest for tetracycline (76 %), chloramphenicol (86 %), and ampicillin (85 %). Serotypes Typhimurium, Newport, and Dublin exhibited lower susceptibility compared to other serotypes. Susceptibility to all antimicrobials increased during the periods 2013–2017 and 2018–2022 compared to isolates before 2012, with a greater increase in 2018–2022. MICs decreased for most antimicrobials except for chloramphenicol and gentamicin, which showed increased median MIC for the periods 2013–2017 and 2018–2022, respectively. In conclusion, antimicrobial use restrictions appear correlated with a reduction in Salmonella AMR, although this effect cannot be untangled from the effect of time in this dataset.